El pensamiento educativo de John Locke y la atención a la educación física (2006)
ABSTRACT: John Locke and the attention to the Physical Education» explains the John's thought Locke (1632-1704) in what refers to the education. In a first moment, the author's contextual and theoretical budgets are presented in connection with the concept of idea and the place of the experience. In a second moment, it is exposed, in a descriptive way, the education conception in John Locke, as Education 'Physics', 'Moral' and 'Intellectual'